2019
DOI: 10.23736/s0026-4806.19.06108-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in chronic hepatitis C long-term responders to pre-direct antiviral agents: a single-center retrospective study

Abstract: Background. Obesity, type 2 diabetes (T2D), dyslipidemia, arterial hypertension as well as hepatic steatosis (HS) are common conditions that can affect clinical outcomes of patients with chronic hepatitis C (CHC) who achieved sustained virological response (SVR). The aim of this study was to assess the impact of metabolic cofactors on the occurrence of clinical events during follow-up (FU) in a group of CHC long term responders (LTRs) to interferon (IFN)-based therapy. Methods. A total of 5172 medical records … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…HCV can also infect and replicate in other cell types, such as peripheral blood mononuclear cells (PBMCs) and bone marrow cells through cell-to-cell transmission[ 22 ]. HCV infects PBMCs and other cells through the interaction with CD81 molecules on the cell surface[ 23 ], allowing replication of HCV in the extrahepatic tissues, which is facilitated by the expression of miR-122[ 24 ]. B lymphocytes, particularly CD27+ memory B cells, can resist apoptosis and may serve as an HCV reservoir[ 25 ].…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…HCV can also infect and replicate in other cell types, such as peripheral blood mononuclear cells (PBMCs) and bone marrow cells through cell-to-cell transmission[ 22 ]. HCV infects PBMCs and other cells through the interaction with CD81 molecules on the cell surface[ 23 ], allowing replication of HCV in the extrahepatic tissues, which is facilitated by the expression of miR-122[ 24 ]. B lymphocytes, particularly CD27+ memory B cells, can resist apoptosis and may serve as an HCV reservoir[ 25 ].…”
Section: Hepatitis C Virusmentioning
confidence: 99%
“…Before the NAFLD epidemic, the most frequently identified liver diseases worldwide were chronic hepatitis B and C 13 . Patients with hepatitis C and a sustained virological response with steatosis present worse extrahepatic outcomes such as cardiovascular events and T2DM 14 …”
Section: Nafld and Investigation Of Comorbiditiesmentioning
confidence: 99%
“…It would be interesting if Piekarska et al could provide us with the patients' co-morbidities, mainly diabetes mellitus, chronic kidney disease, hypertension and obesity, as they might have an impact on their results [1]. Another recently published retrospective analysis demonstrated that the presence of hepatic steatosis in a large cohort of patients with chronic HCV infection increased almost 4-fold the risk of development of cardiovascular disease (HR: 5.2, 95% CI: 1.3-20.7), emphasizing the importance of timely and targeted counselling and multilevel assessment of these patients [8]. In the study by Piekarska et al, 4 patients with chronic HCV infection and concomitant CAD exhibited hepatic fibrosis; however, no data on hepatic steatosis are provided [1].…”
Section: Dear Editormentioning
confidence: 99%